PENERAPAN PENDEKATAN PROBLEM POSING MODEL SEARCH, SOLVE, CREATE AND SHARE (SSCS) TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS XI IPS MAN 1 MODEL BUKITTINGGI - Febrianti, Nola; Yenti, Isra Nurmai; Asmendri, Asmendri (Jurnal Pembelajaran MIPA, 2014)
The research was based on the low of mathematic reasoning ability. Reasoning ability is one of basic ability that mush be achieved by student through mathematic learning. To solve this case, problem posing model SSCS approache is preicted to be able to improve student mathematic reasong ability. This reaserch is quasy experiment reaserch with Randomized Control Group Only Design. Experiment class is given the learning by problem posing model SSCS approache, otherwise, control class is given the conventional lerning. Based on the reasult of data analysis, is concluded that student mathematic reasoning ability on application of problem posing model SSCS approache is better than student mathematic reasoning ability on conventional leraning.Key words: Reasoning ability, problem posing, model SSCS approache